Marketing mix affecting the consumers’ decision in drinking fresh coffee in the Provincial Tourism in the Gulf of Thailand - Lalhalert, Phitchayaphon; Chaidirek, Piset (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
This research aimed to 1)study the marketing mix affecting the consumers’ decision in drinking fresh coffee in the Provincial Tourism in the Gulf of Thailand2)study the consumers’ behaviors in decision making in drinking fresh coffee in the Provincial Tourism in the Gulf of Thailand3) to compare the marketing mix affecting the consumers’ decision in drinking fresh coffee in the Provincial Tourism in the Gulf of Thailand, sorted by personal factors and4) study the relationship between the marketing mix and the consumers’decision in drinking fresh coffee in the Provincial Tourism in the Gulf of Thailand. The samples were the groups of people aged between 25-41 years old, affecting the consumption decision in drinking fresh coffee in Cha-am district and HuaHin district and HuaHin district with total amount of 400 people. Tools used in the study were query as Rating Scale. The statistics used in data analysis were percentage, means, standard deviation and the hypothesis was tested by t-test and ANOVA and Chi-Square Test. The results showed that: 1. The marketing mix affecting the consumers’ decision in drinking fresh coffee in the Provincial Tourism in the Gulf of Thailand, in 7 aspects was at high level. When considering in each aspect, the most was marketing promotion, followed by prices, service processes, distribution channels, products, personnel, and physical environment respectively. 2. The consumers’ behaviors in decision making in drinking fresh coffee in the Provincial Tourism in the Gulf of Thailand, it was found that the purpose in consuming fresh coffee, mostly consumed regularly 53.50 percent, the amount of coffee consumed each day for one glass representing 59.25 percent, consumed in the afternoon (13:00 to 15:59 hrs.) representing 59.50 percent, favored to drink blended coffee equivalent to 46.00 percent, consumption with family 55.25 percent, it was found that the price of fresh coffee was61-80 baht per glass representing 42.00 percent, times spent in the coffee shop in each time took 2-3 hours, representing 37.50 per cent. 3. The comparison of the marketing mix affecting the consumers’ decision in drinking fresh coffee in the Provincial Tourism in the Gulf of Thailand, sorted by personal factors, it was found that the working-age population who had differences in gender, age and occupation, in the overall ,had no different opinions on of the marketing mix affecting the consumers’ decision in drinking fresh coffee in the Provincial Tourism in the Gulf of Thailand. And the working-age population, who had differences in educational level and income, had different opinions on the marketing mix affecting the consumers’ decision in drinking fresh coffee in the Provincial Tourism in the Gulf of Thailand with statistically significant at the 0.05 level. 4. The consumers’ behaviors in decision making in drinking fresh coffee in the Provincial Tourism in the Gulf of Thailand, including the purpose in drinking fresh coffee, quantity of fresh coffee consumed in each day, duration of consuming fresh coffee regularly, types of fresh coffee popularly consumed, whom drank fresh coffee with, prices of fresh coffee and time used to take a coffee at a time, were associated with marketing mix of the fresh coffee shop in the Provincial Tourism in the Gulf of Thailand with statistically significant at the 0.05 level. Article history : Accepted 28 October 2015 SIMILARITY INDEX = 1.06